Enhancing scientific knowledge to support the exploitation of invasive Anadara spp. in the Adriatic Sea - Marina Chiappi; Ernesto Azzurro; Pierluigi Strafella; Carmen Ferrà; Francesca Luzi; Stefano Guicciardi; Giorgio Mancinelli; Alessio Bonaldo; Antonina De Marco; Beatrice Fracasso; Sara Mancarella; Chiara Roberta Girelli; et al. (Marine Policy, 2025)

Uncovering unmet demand and key insights for the invasive blue crab (Callinectes sapidus) market before and after the Italian outbreak: Implications for policymakers and industry stakeholders - Ernesto Azzurro; Sara Bonanomi; Marina Chiappi; Rocco De Marco; Gian Marco Luna; Matilde Cella; Stefano Guicciardi; Francesco Tiralongo; Andrea Bonifazi; Pierluigi Strafella (Marine Policy, 2024)

First occurrence and composition assessment of microplastics in native mussels collected from coastal and offshore areas of the northern and central Adriatic Sea - Alessio Gomiero; Pierluigi Strafella; Kjell Birger Øysæd; Gianna Fabi (Environmental Science and Pollution Research, 2019)

Comparative Effects of Ingested PVC Micro Particles With and Without Adsorbed Benzo(a)pyrene vs. Spiked Sediments on the Cellular and Sub Cellular Processes of the Benthic Organism Hediste diversicolor - Alessio Gomiero; Pierluigi Strafella; Giulio Pellini; Vera Salvalaggio; Gianna Fabi (Frontiers in Marine Science, 2018)

Anadara kagoshimensis (Mollusca: Bivalvia: Arcidae) in Adriatic Sea: morphological analysis, molecular taxonomy, spatial distribution, and prediction - PIERLUIGI STRAFELLA; ALICE FERRARI; GIANNA FABI; VERA SALVALAGGIO; ELISA PUNZO; CLARA CUICCHI; ANGELA SANTELLI; ALESSIA CARIANI; FAUSTO TINTI; ANNA NORA TASSETTI; GIUSEPPE SCARCELLA (Mediterranean Marine Science, 2017)
Morphological analysis, molecular characterization, and information on distribution and density of Anadara kagoshimensis (Tokunaga, 1906) specimens collected in the Adriatic Sea were here carried out as based on various material and data from five surveys conducted from 2010 to 2014, for a total of 329 bottom trawl hauls. The morphological and molecular analyses allowed to clarify the confused taxonomy regarding the biggest ark clam alien species invading the Italian waters and the Mediterranean Sea. The analysis on distribution and density revealed that A. kagoshimensis mostly occurs along the Italian coast at depths from 8 to 50 m, with a catch frequency of more than 98% in all hauls performed on silty-clay sediment at 8-30 m depth. The hotspot map clearly shows a reduction of its distribution area from 2010 to 2012.